The Sound of Unsaid Words: Rethinking the Perception of Silence in Poetry - Ben Zid, Mounir Jilani (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Most scholars and literary critics, whether adhering traditionally to the iron-clad rules of language or enhancing creativity seem to marginalize personal silence or fail to perceive it as a type of discourse. This research is an attempt to subvert established notions of silence and proposes a paradigm that reaches beyond the sound of words and the epidermis of texts. It identifies important hidden dimensions of language, calls for a deeper exploration of the language of silence, and argues that silence in poetry is not simply the absence or opposite of sound. It should be viewed instead as the beginning of listening, a means of communicating the unsaid and the unheard of language as well as the power which privileges the poet's desire for the impossible through "les mots jamais dit". Based on examples from poems, the paper will address silence as the eloquent outpouring of sound and meaning, and as a better language for the unsaid.